Local pragmatics in a Gricean framework, revisited: response to three commentaries. Issue 5 (4th July 2017) - Simons, Mandy
Abstract: There are two central themes that occupy the commentaries, and hence this response. The first is the character and role of what is said, both in my account, and in pragmatic theory in general. In response, I lay out in more detail the proposal from my original paper that the starting point for Gricean reasoning should be not what is said, but the pragmatically uncommitted what is expressed . As part of this argument, I restate and provide further arguments for my claim that global and local pragmatic effects are continuous. The second central theme of the commentaries concerns the value of a Gricean account, which is not intended to model the psychological processes of interpretation. I respond to this concern in Section5, 'Pragmatics, psychology and processing'.